School attendance and sexual and reproductive health outcomes among adolescent girls in Kenya: a cross-sectional analysis - Sai Surabi Thirugnanasampanthar; Lonnie Embleton; Erica Di Ruggiero; Paula Braitstein; Clement Oduor; Yohannes Dibaba Wado (BMC, 2023)
Plain Language Summary Adolescent girls in Kenya experience poor sexual and reproductive health outcomes (SRH) and have low levels of educational attainment. In this study, we aimed to examine if school attendance was associated with sexual and reproductive health outcomes among adolescent girls aged 15 to 19 years in Homa Bay and Narok counties in Kenya. The study used data from the evaluation of the In Their Hands (ITH) program which occurred between September to October 2018. A total of 1840 adolescent girls years participated in the baseline survey, of which 1810 were included in this study. We found that compared to adolescent girls in-school, those who were out-of-school were significantly more likely to report ever having sex, less likely to have used a condom during their last intercourse, and more likely to have ever been pregnant. This study found that attending school plays an important protective role in the SRH of adolescent girls. Therefore, it is important to develop and implement initiatives to support adolescent girls' school attendance, and ultimately their education attainment.